ON CLINIC-LABORATORY FEATURES OF THE COURSE OF ACUTE PURULENT-DESTRUCTIVE LUNG DISEASES IN PATIENTS UNDERGOING SARS-CoV-2. - Bobokulova, Sh.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. The frequency of registration of acute purulent-destructive lung diseases in patients with SARS-CoV-2 during the pandemic was ambiguous. A study on the features of the clinical, radiological, and microbiological manifestations of purulent-destructive lung diseases in patients with SARS-CoV-2 deserves close attention. Material and methods. The results of a comprehensive examination and treatment of 65 patients with acute purulent-destructive lung diseases who underwent SARS-CoV-2 in 2020 are analyzed. Conclusion. When determining the severity of the condition of patients with acute purulent-destructive lung diseases after suffering SARS-Co V-2, the true picture can be obtained only by applying the criteria of septic complications, because the organ failure and/or dysfunction considered to reflect the true picture of the development of the purulent-inflammatory process.